Social Interaction Patterns of the Disabled People in Asymmetric Social Dilemmas - Liu, Shen; Xie, Wenlan; Han, Shangfeng; Mou, Zhongchen; Zhang, Xiaochu; Zhang, Lin (Frontiers in Psychology, 2018)
The social participation of the disabled people is unsatisfactory and low, one of the reasons often overlooked but of great importance may lie in the disparate patterns of social interaction between the disabled people and the abled people. The current study respectively recruited forty-one and eighty disabled people in two experiments and adopted give-some games and public good dilemma to explore social interaction patterns between the disabled abled people. The results were as follows: (1) the disabled people preferred to interact with the disabled people and the abled people preferred to interact with the abled people. (2) The disabled abled people had higher cooperation, satisfaction and sense of justice when interacting with the disabled people than interacting with the abled people. (3) Advantage in the number of the disabled people could reverse their disadvantage in the identity. These results are of important practical value, which provides related theoretical support for the disabled people’s federation and communities when carrying out activities for the disabled people.